The effectiveness of combined lime and alum in osmofilter paper package for improving the quality of peat water - Estri Sutris Neng Asih; Budijono '; M. Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The peat water has low pH and it can be improved by adding lime and alum. The use of lime, however, produced relatively large amount of sediment. To understand the effectiveness of combined lime and alum in osmofilter paper package to increase the pH and reduce the sediment, a study has been conducted on January-April 2016.Combination of 1.7 g lime and 1.45 g alum were wrapped using osmofilter paper and were immersed in 8 L of different pH (2, 3, 4, 5, and 6) peat water. After being kept for 45 minutes, the water quality was checked. Result shown that the package of lime and alum was effective to improve the pH and reduced the sediment. In all treatments the pH increase up to 9, while the sediment decrease, from 38.34 to 34.34. The treated water was use to rear Cyprinus carpio and Oreochromis niloticus seedlings. By the 4th day the survival rate of both fish species was 90 %. Based on data obtained, it can be concluded that the use of combined lime, alum and osmofilter paper is effective to improve the quality of peat water.Keyword : Peat Water, Osmofilter paper, Alum, Lime